LEARNING OF BEHAVIORAL ASSESSMENT IN THE CLINICAL AREA FOR STUDENTS OF PSYCHOLOGY: IMPLICATIONS FOR THE ESTABLISHMENT OF A COMPUTER BASED TRAINING SYSTEM - Rubio, Víctor J.; Santacreu Mas, José; García Rodríguez, Luis Francisco (Anales de Psicología / Annals of Psychology, 1999)
This paper presents the first efforts to design a Computer-based Training system to help students to learn behavioural assessment in clinical settings. The objective of this research was to determine the student systematic errors when they cope to the task. The process of behavioural assessment was divided in the different phases and they was analysed in terms of selection information items, sequence, and integration and manipulation of the information. Students were contrasted to an expertise clinical psychologist to establish the process phases in which they have problems and the more common errors. Data show these systematic errors and suggest training strategies which could be useful to design a Computerbased Training system and its implementation on the learning- instruction process and its evaluation.